Simulasi Model Material Tanah Pada Bidang Gelincir Longsor Dengan Variasi Sudut Kemiringan (Studi Kasus Material Tanah di Daerah Kabupaten Gorontalo Utara) - Rabiyatul Hajar Saleng; Asri Arbie; Dewa Gede Eka (Jurnal Teori dan Aplikasi Fisika, 2024)
Landslides are one of the geological disasters that often occur in Indonesia. North Gorontalo is an area where landslides occur every year. Based on data from the 2022 Badan Penanggulangan Bencana Daerah (BPBD), in the last year, there were 8 landslides. Landslides can occur due to several factors, namely; human factors and natural factors. In principle, landslides occur when the restraining force is less than the driving force. In this study a landslide simulation will be carried out using a simulation model made on a lab scale, the size of the simulation model is 40 cm x 30 cm x 25 cm. The simulation was carried out using soil samples taken at the research location. Variables that were observed during the simulation were the effect of the slope angle (o) on the exiting water (ml), the water infiltration time (t), and the effect of the slope (o) on the depth of the slip plane (cm). The soil taken from the research location will be subjected to a sieving analysis test with a hydrometer test to determine the texture class of the soil. From the soil texture test results, some of the research locations have a sand-gravel type of texture. The simulation test carried out also obtained the result that the slope of the slope greatly influences the water infiltration time with the depth of the slip plane. The greater the angle of the slope of the sled that is carried out, the results of the variable being measured will also be directly proportional.